2018
DOI: 10.1097/jtn.0000000000000355
|View full text |Cite
|
Sign up to set email alerts
|

Continuing Trauma Care After Discharge, the Experience of Outpatient Trauma Clinics in British Columbia

Abstract: The recovery process from traumatic injuries, and the potential for complications, extends beyond the time of hospital discharge. In 2014, the Fraser Health Trauma Network established outpatient clinics to provide follow-up care for trauma patients after discharge from hospital. The following research questions were asked: Which services were commonly performed by our trauma clinics and how satisfied were patients with the care they received at our clinics? A survey was distributed to patients after their clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…One study who reported on two follow-up clinics as part of the same health organisation, found a reduction in both the presentations (from 6.4% to 5.1%) and readmission rates (from 7.1% to 6.5%). 44 …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…One study who reported on two follow-up clinics as part of the same health organisation, found a reduction in both the presentations (from 6.4% to 5.1%) and readmission rates (from 7.1% to 6.5%). 44 …”
Section: Resultsmentioning
confidence: 99%
“…In both studies the advanced qualifications were specific to the psychologists involved in the team. In relation to the nursing roles, studies described educational levels in terms of the position title or experience: nurses were described as experienced35 having additional qualifications such as a nurse practitioner38 43 44 or advanced practice nurse 37…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations